Saturday

December 20, 2014

December 20, 2014

Posted by **valua patterson** on Sunday, May 29, 2011 at 8:11pm.

- math -
**Reiny**, Sunday, May 29, 2011 at 9:24pmfor 2x^2 - 6x + 7 = 0

the sum of the roots = -b/a = 6/2 = 3

product of the roots = c/a = 7/2

so (7/2)(3) = 21/3

**Answer this Question**

**Related Questions**

Math - 1. The expression log 5x is equivalent to 2. Write the equation of a ...

Algebra - Given the roots, 1/2 and 4, find: (A) The quadratic equation 2x^2-9x+4...

math urgent - Find the result if the sumn of the roots of y= x^2+3x-5 is added ...

Math - Roots Ok, what about roots? Roots of polynomials? Square roots? Cube ...

math - the function with the sum of roots of 11 and product of roots is 11 is...

Alg 2 - By what amount does the sum of the roots exceed the product of the roots...

Algebra - The equation x^2+px+q=0, q cannot be equal to 0, has two unequal roots...

amath - The roots of the quadratic equation x^2-mx+n=0 ,where m and n are ...

Math - The equation x^2+px+q=0, q cannot be equal to 0, has two unequal roots ...

further mathematics - The roots of the eqn, x^4 + px^3 + qx^2 + rx + s = 0 where...